Abu Dhabi children’s Library as a Knowledge Hub for Innovation and Lifelong Learning - Sameera Abdullah (22149904) (2025)
This Presentation was given by Dr. Sameera Abdullah. Reclaiming Trust: Libraries in the MENA Region and the Future of Information Integrity/United Arab Emirates University (Uniting Knowledge, Building the Future World Library and Information Congress 89th IFLA General Conference and Assembly 2025) Abu Dhabi Children’s Library as a Knowledge Hub for Innovation and Lifelong Learning” highlights the library’s pioneering role as an interactive space that blends culture and technology to inspire children and families. It focuses on the Future Roots program, which empowers youth through initiatives such as the Youth Board, the Passport of Tomorrow digital platform, gamified immersive learning, and augmented reality experiences. The library is showcased as a hub that nurtures creativity, critical thinking, cultural identity, and future-ready skills. Other Information Presentation was given at: Reclaiming Trust: Libraries in the MENA Region and the Future of Information Integrity https://2025.ifla.org/caucus-arabic/ License: https://creativecommons.org/licenses/by/4.0/ Conference information: Uniting Knowledge, Building the Future World Library and Information Congress 89th IFLA General Conference and Assembly 2025 https://2025.ifla.org/home/conference-programme/